Hormonally regulated expression of arginine kinase in Drosophila melanogaster. - James, J.M.; Collier, G.E. (Roux's Archives of Developmental Biology, 1990)
Arginine kinase (AK) is present throughout the life cycle of Drosophila melanogaster, but there is a sharp, transient peak of AK activity during the prepupal period and a second period of elevated activity at the time of eclosion of the adult. Imaginal discs show the greatest increase in AK activity at the prepupal stage of those tissues assayed. The prepupal peak is not seen when the temperature-sensitive ecdysoneless mutant ecd-1 is shifted to 29° C at mid-third instar larval stage. The peak in activity reappears when ecd-1 is either shifted back to 20° C after 60 h at 29° C or is fed 20-hydroxyecdysone. At the restrictive temperature, imaginal discs from ecd-1 larvae progressively lose AK activity, whereas discs from 20-hydroxyecdysone-fed larvae have a marked increase in AK activity at stage P3 of the prepupal period. These data suggest that the prepupal peak is regulated by the hormone 20-hydroxyecdysone.